Next-generation sequencing (NGS) to determine microbiome of herniated intervertebral disc - Astur, Nelson; Maciel, Brenno Ferreira Bento; Doi, Andre Mario; Martino, Marines Dalla Valle; Basqueira, Marcela Souza; Wajchenberg, Marcelo; Lenza, Mario; Martins, Delio Eulalio (The spine journal, 2022)
•A novel use for Next Generation Sequencing (NGS) testing was made to determine the intervertebral disc microbiome•Once considered a sterille tissue, the intervertebral disc presented a microbiome, although the very low rates of bacterial sequences mapped questions the relevance of this result.•Despite being extensively reported as the cause of subclinical infection of the disc, Cutibacterium acnes was not found in any disc microbiome analysis. There is apparent causality between chronic infection of the intervertebral disc and its degenerative process. Although disc is considered a sterile tissue, collected samples of uninfected patients sent to culture testing resulted positive. The purpose of this study was to analyze the microbiome of the intervertebral disc by using and validating the next-generation sequencing (NGS) molecular test, controlled with tissue culture and clinical presentation of patients. Prospective study of consecutive patients in a hospital. Patients with lumbar disc herniation undergoing open microdiscectomy aging 18 to 65 years. NGS, tissue culture Subjects undergoing open decompression surgery for lumbar disc herniation were consecutively included and clinically followed for one year. Three samples of the excised herniated disc fragment were sent to tissue culture and another sample of the disc was sent to NGS test for microbiome analysis. Control samples of the ligamentum flavum and deep muscle were collected and sent to culture. A total of 17 patients were included. All patients presented negative cultures of the removed disc samples, as well as negative cultures of muscle and yellow ligament. None of the patients evolved to clinical infection one year after surgery, nor presented significant alteration of laboratory markers. NGS mapped a mean of 14,645 (range 6,540 to 27,176) DNA sequences for each disc sample of each patient. There were a total of 45 different bacteria genera remnants with different amount of DNA sequences detected. There was a mean of 8 (range 3-17) different bacterial elements in each sample of intervertebral disc. Three bacteria were present in all disc samples (Herbaspirillum, Ralstonia, and Burkolderia). Although there were a considerable mean number of bacterial sequences mapped in each disc sample, the amount of sequences related to bacteria was low. Cutibacterium acnes elements was not found in any disc microbiome analysis. NGS has been proven to adequately determine bacterial DNA presence within the intervertebral disc. C. acnes was not isolated in culture neither in microbiome analysis of patients with lumbar disc herniation. We cannot confirm disc sterility since, even if it does not cause infection, there is bacterial or remnant DNA in herniated discs.